Pengembangan bahan ajar bahasa Sasak berbasis high order thingking skills - Taufiqqurrahman Taufiqqurrahman; Efendi, Mohammad; Sulton, Sulton (Jurnal Teori dan Praksis Pembelajaran IPS, 2017)
The research objective is to produce and test the feasibility of textbooks based Sasak language thingking high order skills for junior high school students. The model used is a model development Dick, Carey & Carey until the ninth stage. The product development is validated by subject matter experts with a level of validity 73 percent, media experts with a degree of validity of 84 percent, a learning design with a level of validity 90.4 percent, individual testing with a level of validity of 68 percent, small group trials with a level of validity 82 percent, and test field trials with a validity rate of 89 percent with a very worthy qualification that does not need revision.